Manejo do solo e utilização de bioestimulante no tratamento de sementes de trigo (Triticum aestivum L.) - Navarini, Luciano Leite (2010)
Provide good conditions to the growth of plant root system is the object in soil tillage. Technologies have been proposed in order to minimize adverse conditions to, increasing plant yield. This study aimed at evaluating the effect of different soil managements and plant growth biostimulants use on wheat seed treatment. The experiment consisted of three soil management (no-tillage - NT, notillage chiseled - NTC, plowed) and three seed treatments (Stimulate®, Booster® and control) allotted to a randomized block design, with split plot arrangement. The physical-hydric attributes (bulk density, total porosity, soil pore size distribution, relative bulk density and least limiting water range), yield components were evaluated. The least limiting water range (LLWR) for the same density was higher under NTC than NT and plowed. The relative density when LLWR is zero was 0,94 for NT and NTC and 0,93 for plowed. The higher wheat grain yield was obtained under NTC and plowed management differing from NT. Biostimulants used via seed did not influence the yield components, as well as, there was not statistical difference in yield among treatments with biostimulants and control. It was concluded that soil tillage under NT increases wheat grain yield and 4 biostimulants use does not affect yield components neither wheat grain yield